Implementation of insecticide-treated malaria bed nets in Tanzania: a systematic review - Obidimma Ezezika; Yasmine El-Bakri; Abitha Nadarajah; Kathryn Barrett (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Malaria is a significant cause of morbidity, mortality, and economic burden among the Tanzanian population. An effective form of personal protection against malaria is the insecticide-treated bed net (ITN). Although Tanzania has made great efforts to implement ITNs in the general population, gaps in use, access, coverage, and ownership remain. We conducted a systematic review of the available data on the barriers and facilitators to the implementation of ITNs in Tanzania. # Methods A comprehensive search was conducted in four databases: OVID Medline, OVID Embase, EBSCO CINAHL, and Web of Science. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed to present the review and analysis. Eligible studies were appraised to determine the quality of evidence. Various content data were extracted, including study locations, years of publication, study objectives, and barriers and facilitators to ITNs. The Consolidated Framework for Implementation Research (CFIR) facilitated a thematic analysis of the barriers and facilitators. # Results Seven mixed-methods and three qualitative studies met this review's inclusion criteria. Seven regions and ten districts within Tanzania were represented in this review, most notably the Morogoro region and its respective districts, Kilombero and Ulanga. Study dates ranged from 1995 to 2020. Facilitators of ITN implementation included cost, voucher schemes, involving locals, planning for distribution, and social marketing and communication campaigns. Similarly, barriers to ITN implementation included cost, knowledge and beliefs, a poorly developed private sector, and inadequate distribution methods. # Conclusions A systematic review of studies on the implementation of ITNs in Tanzania highlights vital areas in the development of successful implementation that include: (i) the cost of ITNs, (ii) knowledge and beliefs about ITNs among potential users, and (iii) planning for the execution of ITN distribution programs. ITN implementation can be enhanced if national stakeholders invest further in processes that promote ITN procurement, such as voucher schemes, providing education sessions, integrating distribution methods that cater to locals' preferences, and initiating the promotion of ITN months in advance of their distribution. # Registration PROSPERO (https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=222128)